Problems of Concretization of Legal Norms in Kazakhstan - BEISBEKOVA, Gulim Kuatbekovna; KONUSSOVA, Venera Tuleutaevna; ISMAGULOV, Kairat Eslyamkalievich; SAKTAGANOVA, Indira Sovetovna; MUKASHEVA, Anar Abaikhankyzy (Journal of Advanced Research in Law and Economics; Vol 10 No 1 (2019): JARLE Volume X Issue 1(39) Spring 2019DO - 10.14505//jarle.v10.1(39).07, 2019)
The study of ways to improve the quality of legal regulation is of particular relevance in modern conditions. As the practice of legal regulation confirms, one of the factors for the improvement of legality and efficiency is concretization of legal norms. The article points out that despite a fairly high level of knowledge today there are problems of lack of unity in understanding the essence and legal nature of concretization of law in general theoretical jurisprudence, terminological inconsistency of the concept of concretization of legal norms and criteria for distinguishing this phenomenon from related interpretation and analogy of legal concepts.